2022
DOI: 10.1136/ard-2022-222554
|View full text |Cite
|
Sign up to set email alerts
|

Site of invasion revisited: epigenetic drivers of joint destruction in RA

Abstract: New analytical methods and the increasing availability of synovial biopsies have recently provided unprecedented insights into synovial activation in general and synovial fibroblast (SF) biology in particular. In the course of this development, SFs have become one of the most rapidly evolving and exciting fields of rheumatoid arthritis (RA) research. While their active role in the invasion of RA synovium into cartilage has long been studied, recent studies have brought new aspects of their heterogeneity and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Bone erosion in RA patients develops as the disease progresses, leading to joint damage and dysfunction. [ 95 ] The tissue repair mechanisms mainly include two aspects. First, MSCs down‐regulate osteoclast generation and pro‐inflammatory cytokines through paracrine action, and inhibit bone and cartilage erosion in RA.…”
Section: Promotion Of Tissue Regenerationmentioning
confidence: 99%
“…Bone erosion in RA patients develops as the disease progresses, leading to joint damage and dysfunction. [ 95 ] The tissue repair mechanisms mainly include two aspects. First, MSCs down‐regulate osteoclast generation and pro‐inflammatory cytokines through paracrine action, and inhibit bone and cartilage erosion in RA.…”
Section: Promotion Of Tissue Regenerationmentioning
confidence: 99%
“…It is well established that RASF are epigenetically modified early in the course of RA leading to an inflammatory and matrix-degrading phenotype. Findings of epigenetic alterations of RASF have been summarized regularly and in recent reviews [3,19], including the highly interesting special focus on cartilage invasion [2]. Of note, it could be shown that transporters of amino acids and other nutrients were associated with certain epigenetic marks in RASF using an approach comparing differences in genome-wide states and gene transcription between RA and osteoarthritis (OA) [20].…”
Section: Rheumatoid Arthritis Synovial Fibroblasts Are Activated By P...mentioning
confidence: 99%
“…In rheumatoid arthritis (RA), a chronic inflammatory joint disease, the synovial tissue in affected joints is inflamed leading to an influx of inflammatory cells contributing to the formation of an inflammatory environment within the tissue. In RA, synovial fibroblasts are activated because of the inflammatory milieu already at very early stages of the disease, mediated by epigenetic alterations in RA synovial fibroblasts (RASF), resulting in a permanently activated stage of these cells [2][3][4]. Due to the synovial hyperplasia and inflammatory processes, the synovial tissue gets in direct contact with the cartilage tissue allowing the invasion of activated RASF into the cartilage matrix.…”
Section: Introductionmentioning
confidence: 99%
“…I would also like to direct you to the excellent review by Ospelt on epigenetic factors that drive joint damage 22. And as always, papers on many topics in rheumatology, from rheumatoid arthritis to macrophage activation syndrome complement this issue.…”
mentioning
confidence: 96%